2015
DOI: 10.1159/000440887
|View full text |Cite
|
Sign up to set email alerts
|

Glia-Mediated Retinal Neuroinflammation as a Biomarker in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is the most common type of dementia worldwide; it is characterized by a progressive decline in cognitive functions and memory, resulting from synaptic and cell loss, and accompanied by a strong neuroinflammatory response. Besides the vast progress in the understanding of the pathophysiology of AD in the past decades, there is still no effective treatment. Moreover, the diagnosis occurs usually at an advanced stage of the disease, where the neurological damage has already occurred. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…In AD, microglial activation in the brain has been demonstrated, indicating that a neuroinflammatory process occurs in this disease [5,35]. In a normal adult nervous system, microglia are found in a quiescent state characterized by a ramified morphology [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AD, microglial activation in the brain has been demonstrated, indicating that a neuroinflammatory process occurs in this disease [5,35]. In a normal adult nervous system, microglia are found in a quiescent state characterized by a ramified morphology [36].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, during disease progression, the anti-inflammatory profile changed to a pro-inflammatory one, allowing potentially neurotoxic genes to be overexpressed (iNOS, IL-1β) [27]. Therefore, chronic activation of the microglia, with a constant release of proinflammatory factors, could cause a decrease in both Aβ phagocytosis and neurotoxicity, which would lead to neuronal death [35].…”
Section: Discussionmentioning
confidence: 99%
“…Retinal pathology has recently been intensively discussed in the context of Alzheimer disease, Parkinson disease, and amyotrophic lateral sclerosis (39, 40). Furthermore, unprecedented breakthroughs are possible in the context of pathologies such as genetic vasculature diseases and diabetes type I (41, 42), which are associated with changes of the retinal vasculature, including main blood vessels and capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…AD is a progressive neurodegenerative disease characterized by a decline in cognitive function and memory resulting from synapse and cell loss, accompanied by a strong neuroinflammatory response. It accounts for 60–80% of dementia cases, and is the leading cause of these in the population over 60 years old 2 …”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…It has been shown that both microglia and astrocytes, not neurons, are the main source of N-terminally truncated Aβ peptides that can be found in amyloid deposits 2 . Aβ plaques stimulate the factors and proteins that induce the production of inflammatory cytokines and chemokines.…”
Section: Neurodegeneration Glial Response and Alzheimer'smentioning
confidence: 99%